Formation kinetics of sol-gel derived LiFePO4 olivine analyzed by reliable non-isothermal approach. Issue 12 (15th June 2022) - Amri, Amun; Hendri, Yola Bertilsya; Saputra, Edy; Heltina, Desi; Yin, Chun-Yang; Rahman, M. Mahbubur; Minakshi, Manickam; Mondinos, Nicholas; Jiang, Zhong-Tao
Abstract: The formation kinetics of LiFePO4 Olivine synthesized through sol-gel route has been studied by non-isothermal approach. LiFePO4 precursors were prepared by mixing lithium dihydrogen phosphate (LiH2 PO4 ) and iron (III) citrate (C6 H5 FeO7 ) and subsequently calcined in an Argon atmosphere at temperatures ranged from of 300–900 °C to form LiFePO4 products. Thermal behaviors of calcination process were analyzed by thermogravimetry (TGA) and differential scanning calorimetry (DSC) simultaneously, while the mineralogical properties of LiFePO4 were characterized using X-ray diffractometer (XRD). The kinetic parameters were determined by Ozawa–Flynn–Wall (OFW), Kissinger, and Kissinger-Akahira-Sunose (KAS) methods, and the reaction mechanism model was evaluated by Coats–Redfern approach. The results indicated that the reaction model of LiFePO4 formation agreed with the three-dimensional diffusion mechanism. The temperature had an essential role in the synthesis of LiFePO4 . The optimum calcination temperature was 700 °C where this condition produced LiFePO4 Olivine with high degree of crystallinity, better lattice parameters and phase purity.